AN ANALYSIS OF TEXT WRITING ACQUISITION BY PRE-SERVICE TEACHERS - Ida Ayu Made Sri Widiastuti; Ida Bagus Nyoman Mantra; Ni Made Wersi Murtini (Denpasar Institute, 2020)
Writing is a complex process in which the process of putting the ideas and organizing the grammatical sentences into written statements as a means of communication. The study dealt with analyzing text writing acquisition by pre-service teachers in Bali. The samples were 60 pre-service teachers who are currently taking teachers training in the English language education study program. The participants were determined using a random sampling method with a lottery system. The data were collected by administering an essay text writing instrument. The obtained data were analyzed by using a norm-referenced measure of five standard values showed that 0.00% of the samples got excellent achievement of recount text writing ability; 41.67% of the samples got good achievement; 30.00% of the samples got sufficient achievement; 18.33% of the samples got the insufficient achievement, and 10.00% of the samples got the poor achievement. This indicated that 71.67% of the samples who were categorized successfully in text writing and the other 28.33% samples were categorized unsuccessful as they were below the sufficient achievement. This finding implies that further serious training in text writing should be undertaken by pre-service teachers.